Metamemory ratings predict long-term changes in reactivated episodic memories - Yacoby, Amnon; Dudai, Yadin; Mendelsohn, Avi (Frontiers in Behavioral Neuroscience, 2015)
Reactivation of long-term memory can render the memory item temporarily labile, offering an opportunity to modify it via behavioral or pharmacological intervention. Declarative memory reactivation is accompanied by a metamemory ability to subjectively assess the knowledge available concerning the target item (Feeling of knowing, FOK). We set out to examine whether FOK can predict the extent of change of long-term episodic memories by post-retrieval manipulations. To this end, participants watched a short movie and immediately thereafter tested on their memory for it. A day later, they were reminded of that movie, and either immediately or one day later, were presented with a second movie. The reminder phase consisted of memory cues to which participants were asked to judge their FOK regarding the original movie. The memory performance of participants to whom new information was presented immediately after reactivating the original episode corresponded to the degree of FOK ratings upon reactivation such that the lower their FOK, the less their memory declined. In contrast, no relation was found between FOK and memory strength for those who learned new information one day after the reminder phase. Our findings suggest that the subjective accessibility of reactivated memories may determine the extent to which new information might modify those memories.